Implementation of Sharing & Jumping Tasks Learning to Grow Students' Creative Thinking Skills in Buffer Solution - Zestia, Witty; Supriatna, Asep; Nahadi, Nahadi (Journal of Educational Sciences, 2022)
This study aims to identify the growth of students' creative thinking skills in the implementation of learning sharing & jumping tasks in the buffer solution material. The method used in this research is descriptive qualitative. The research was conducted in one of Bandung's high school students of class XI with a total of 24 students. The instruments used for data collection were interview guidelines, audio and video recordings through zoom meetings and observation sheets. The collected data were analyzed based on Transcript Based Lesson Analysis (TBLA). The results showed that in the sharing task all aspects of creative thinking skills emerged during the learning process, namely in the aspects of fluent thinking, flexible thinking, original thinking, elaborative thinking, and evaluative thinking. Meanwhile, in the jumping task, there is one aspect that does not appear, namely the aspect of original thinking.